Community Archaeology in Los Roques Archipielago National Park, Venezuela - Andrzej Antczak (Ksiegarnia Akademicka Publishing, 2021)
Convinced that archaeology as a past‑ oriented discipline should exert a transformative impact on the present, we discuss a series of initiatives that aim at interweaving the past of the Los Roques Archipelago, located 135 km off the central coast of Venezuela, into its present‑ day community life. Pioneering archaeological research carried out on these islands since 1982 revealed an unexpectedly rich volume of diversified artifacts and contextual information on the Amerindian seamen who seasonally exploited the local natural resources between A.D. 1200 and 1500. We are confident that despite the historical discontinuity between the pre‑ Hispanic seamen and the current population of the archipelago, the vibrant and colorful archaeological past will reach the present‑ day inhabitants, enriching their socio‑ cultural identity and influencing their way of life that currently oscillates entrapped between fishing and tourism‑ oriented activities. We discuss the aims and methodology of community archeology activities that include talks, exhibits, publications, documentary films and – above all – archaeological workshops that bring together the archaeologists and Los Roques schoolchildren in experiential archaeological events.